Understanding effectiveness of a low-cost food package for ensuring food security during the COVID-19 at the household level: Difference-in-differences analyses of a quasi-experimental trial in Bangladesh - Md. Golam Rasul; Ar-Rafi Khan; Md. Ashraful Alam; Tahmeed Ahmed; Subhasish Das (PLoS ONE, 2026)
Introduction The emergence of COVID-19 pandemic compelled to undertake a ‘lockdown or shutdown’ approach to control the spread of the virus. People from resource-limited settings experienced food insecurity due to lack of supply and access to adequate food during lockdown. Therefore, we developed a low-cost food package and assessed its effectiveness to improve household food insecurity during the COVID-19 pandemic. Method A food package was developed with low-cost, culturally acceptable foods. Each food basket, designed to support a family of four adults and/or one child for 15 days costs 23 USD. A community-based quasi-experimental intervention study was conducted to evaluate the effectiveness of the food package. A total of 245 participants were enrolled in the intervention group, and 244 participants in the control group. A community-based census was carried out to identify vulnerable households and were randomly assigned to the intervention or control groups. Data was collected to assess changes in food insecurity status using the Household Food Insecurity Access Scale, as well as dietary diversity, food frequency, morbidity, and nutritional outcomes. Results Statistically significant changes (p < 0.05) in food insecurity status were observed in the intervention group before, during, and after the intervention. The proportion of food-insecure households decreased from 45.31% to 7.80%, while the proportion of food-secure households increased from 8.60% to 31.02% after one month of intervention. The Difference-in-Differences (DID) models estimated a 13.10 percentage point improvement in proportions of food-secure households and a 16.20 percentage point reduction in food-insecure households, both of which were statistically significant (p < 0.05). Conclusion A low-cost food intervention improved the food security status of vulnerable families during COVID-19 lockdown. This finding suggests that government and other aid agencies can adopt the developed food package to ameliorate household food insecurity in adverse situations.